TINJAUAN YURIDIS WANPRESTASI PADA TRANSAKSI E-COMMERCE MELALUI SITUS FORUM JUAL BELI KASKUS - , Yuko Fitrian, SH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This researched had an aim to: (1)Knowing how the agreement formed in ECommerce transaction from online shop in kaskus site, (2)Knowing the classification of breach of contract that happen and every effort that could do concerned of breach of contract which is happen in kaskus site, (3)Knowing does the E-Commerce transaction from online shop forum in kaskus site could be the caused breach of contract. Research method used Normative Juridical, which is the material focused on every rule about breach of contract, electronic transaction, and consumer protection. Character of this researched was analytic descriptive. The data resources was secunder data which is consist of legislation rules and other literature. Those data analysis which is used, was data analysis descriptive that consist of data collective, data served, and the conclusion. The conclusions from this researched are: (1)There was agreement formed in e-commerce transaction from online shop forum in kaskus site, that begun from bargaining who given by e-merchant. If two sides are agreed or deal with every main things. Then, there would be formed an agreement between two sides. (2)There were two kind of breach of contract that happen in online shop forum in kaskus site. Both of them were: doing the agreement, but didn`t appropriate with the agreement. Doing the agreement, but late. Meanwhile, the effort that could do in breach of contract where happened on it was peaces arrangement pass through. (3)E-commerce transaction that doing in it site wasn`t be the caused of breach of contract. This is based on personality principle which is one of the law agreement based.